Management of Field Work Practice Programs in Enhancing Students’ Competencies in Vocational Education - Dede Ahmad; Ida Tejawiani (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2026)
Field Work Practice is an important strategy in vocational education to improve students' competencies through workplace learning experiences. However, the effectiveness of PKL implementation is strongly influenced by the quality of program management, including planning, organizing, implementation, and evaluation. This study aims to analyze the management of the PKL program in improving student competencies in vocational high schools. The research employed a qualitative approach with a case study design conducted at SMK Negeri 1 Cugenang and SMK Negeri Pertanian Pembangunan Cianjur. Data were collected through semi structured interviews, passive participatory observation, and documentation study. Data were analyzed thematically through data reduction, data presentation, and conclusion drawing. The results indicate that PKL management is implemented systematically through management functions consisting of industry based planning, organizing through the formation of implementation teams and task distribution, implementation through students involvement in real industrial work activities, and evaluation through competency assessments conducted by schools and industry partners. Although several challenges were identified, such as limited industry partners and variations in student readiness, strategies including strengthening industry partnerships, improving student preparation, and conducting periodic monitoring have enhanced the effectiveness of PKL implementation. The study concludes that systematic and collaborative PKL management plays a significant role in improving students competencies and work readiness in vocational education.